Exploring Factors Driving Experiential Loyalty In Third-Wave Coffee Shop Saya Kopi Nuansa - Ghiffary, Naufal Ahmad; Aprilianty, Fitri (Journal of Business and Management, 2021)
In this pandemic era, many third-wave coffee shops struggle to survive and compete in the market, and one of them is Saya Kopi Nuansa. According to previous studies, improving experiential loyalty can help businesses to compete in the market, as it boosts profits and reduces marketing cost. This research aims to identify the factors driving experiential loyalty in Saya Kopi Nuansa, and examine the influence of experiential quality, experiential satisfaction, perceived value, and experiential trust in the experiential loyalty of Saya Kopi Nuansa customers. This study use quantitative approach through questionnaire-based surveys. The target population was Saya Kopi Nuansa instagram followers, and the sampling technique is purposive sampling. Moreover, preliminary research (semi-structured interviews) were conducted to gain deeper understanding of experiential quality dimensions. The collected data is analyzed using the PLS-SEM method. As for the result, the significant factors influencing experiential loyalty are affective quality, physical environment quality, and outcome quality through experiential quality, perceived value, experiential trust, and experiential satisfaction as mediators. The finding is intended to help Saya Kopi Nuansa to build effective strategies to gain experiential loyalty, and subsequently, compete in the market.Keywords: Affective quality, experiential loyalty, experiential quality, Saya Kopi Nuansa, third-wave coffee shop